ChemInform Abstract: Perfluoroalkyl and ‐aryl Zinc Ate Complexes: Generation, Reactivity, and Synthetic Application. Issue 49 (December 2015) - Wang, Xuan; Hirano, Keiichi; Kurauchi, Daisuke; Kato, Hisano; Toriumi, Naoyuki; Takita, Ryo; Uchiyama, Masanobu
Abstract: A method for the generation of novel unprecedentedly stable perfluoroalkyl zincates is developed and their coupling reaction with a range of diverse carbonyl compounds is studied.